Lengkong in Wong Kalang Residential as a Mitigation Space - Setio, Stefanus Prabani; Putra, Heristama Anugerah (Celt: A Journal of Culture, English Language Teaching & Literature, 2022)
Lengkong is a space between the two traditional houses of the Limasap wong Kalang house. The space is formed based on the distribution of land and the construction of the Limasap house. A legacy of the Kalang ancestors to provide distance between houses for a specific purpose. At this time there has been a shift in the function of the Lengkong space. This shift in function is related to the activities of the residents, both positive and negative. This space becomes a debate when it is used as a space with negative activity. However, Wong Kalang wants the space to remain. The existence of the space has been thought out, planned and conditioned as a useful space. The benefits of this space are also being debated because it reduces the area of Wong Kalang's yard. Through an ethnographic research method approach, researchers describe the benefits of the Lengkong space which is the legacy of the Kalang ancestors. The results of the study found that the benefits of the Lengkong space at this time are still being maintained. These benefits: 1) Social Space; 2) Tradition Room; 3) Mitigation Room. Activities carried out positively provide benefits. Meanwhile, negative activities need to be eliminated through socialization and a humanist approach. At this time, a new benefit of Lengkong space appears as a mitigation space which will be useful if bad things happen to residents and neighbors